Exigência de metionina +cistina total para codornas de corte de dois grupos genéticos - Tatiana Zacche Batista Vidal (2013)
Four experiments were carried out in a completely randomized experimental design to evaluate the effect of total methionine + cystine on the performance and carcass traits of two European quail genetic strains EV1 (experiment 1and 2) and EV2 (experiment 3 and 4) during two phases of the growing period (from hatch to 21 days of age and from hatch to 35 days of age). The first experiment was evaluated in a completely randomized experimental design with six level of total methionine + cystine (.86; .96; 1.06; 1.16;1.26;1.36), four replicates and 15 quails per experimental unit. Body weight, weight gain, feed intake and feed: weight gain ratio were evaluated. Significant quadratic effects of total methionine + cystine level on the performance traits recorded from hatch to 21 days of age were observed. Highest body weight and weight gain were estimated for quails fed 1.21% total methionoine + cystine diets, lowest feed intake was estimated for quails fed 1.36% diets and best feed: weight gain ratio was estimated for quails fed 1.21% total methionoine + cystine diet. The second experiment a total of 288 quails of both sex were allotted in a completely randomized experimental design with six treatments and four replicates of 12 quails per experimental unit. The treatments consisted of six total metionine + cistine diet levels (0.72, 0.82, 0.92, 1,02, 1.12, and 1.22%). The evaluated performance traits were body weight, weight gain and feed: weight gain ratio and the carcass traits were body weight and weights and yields of carcass, breast, thigh, wings, edible giblets and fat pad. Significant quadratic effects of total methionine + cystine effect on all evaluated traits were observed. Maximum body weight and weight gains were estimated for quails fed 0.96% total methionine + cystine diets. A significant interaction between total methionine + cystine and sex for breast weight was observed Significant quadratic effect of total methionine + cystine were observed for body and carcass weights with estimated maximum for quails fed 0.97 and 0.99% total methionine + cystine diets, respectively. A decreasing linear effect of total methionine + cystine diet levels on thigh + drumstick, and an increasing effect on liver weight and yield were observed. Significant interaction effect between total methionine + cystine level and sex for carcass yield was observed. Body, liver and gizzard weights, and liver and gizzard yields were higher in the females. The total methionine + cystine requirement for weight gain from hatch to 21 days of age is 1.21% and the total methionine + cystine requirement for maximum body weight from 21 to 35 days of age is 0.95% and for carcass and breast weights is 0.95%. The third experiment was evaluated in a completely randomized experimental design with six level of total methionine + cystine (.86; .96; 1.06; 1.16; 1.26; 1.36), four replicates and 15 quails per experimental unit. Body weight, weight gain, feed intake and feed: weight gain ratio were evaluated. Significant and quadratic effects of total methionine + cystine on the performance traits recorded from hatch to 21 days of age were observed. Maximum weight and weight gain were estimated for quails fed 1.24% total methionine + cystine diets, 1.36% for lowest feed intake and 1.14% for best feed: weight gain ratio. Weight gain methioninine + cystine requirement from hatch to 21 days is 1.21% equivalent to a total methionine + cystine: lysine ratio equal to 0.71. The fourth experiment a total of 288 quails of both sex were allotted in a completely randomized experimental design with six treatments and four replicates of 12 quails per experimental unit. The treatments consisted of six total metionine + cistine diet levels (0.72, 0.82, 0.92, 1,02, 1.12, and 1.22%). The evaluated performance traits were body weight, weight gain and feed: weight gain ratio and the carcass traits were body weight and weights and yields of carcass, breast, thigh, wings, edible giblets and fat pad. Significant quadratic effects of total methionine + cystine on body weight and weight gain were observed. Maximum body weight and weight gains were estimated for quails fed 0.95 and 1.04% total methionine + cystine diets, respectively. Significant quadratic effect of total metionine + cystine on body and carcass weights were also observed with maximum values for quails fed 1.05% of total methionine + cystine diets. The females were heavier and showed higher liver and gizzard weights than the males. The total methionine + cystine requirement for maximum weight gain in the final phase of the growth period is 1.04 and for carcass and breast weights is 1.05%.